Selection of common bean families adapted to the winter conditions of the South of Minas Gerais State - Nunes, Glauber Henrique de Sousa; Santos, João Bosco dos; Ramalho, Magno Antônio Patto; Abreu, Ângela de Fátima Barbosa (Pesquisa Agropecuaria Brasileira, 1999)
The purpose of the present work was to select common bean families adapted to the winter conditions of South of Minas Gerais State, Brazil. 230 families were selected from segregant populations L3272 x (Carioca x TU) and L3272 x ESAL 601. They were evaluated in the winter crops in the South of Minas Gerais, and the 103 most promising ones were selected. The families selected were divided in two sets. The first, with 79 normal cycle families, and the second, with 24 precocious families, which were assessed in two locations, in 1995. The best 24 families were evaluated in the winter of 1996. The traits considered were grain yield, number of the days to flowering and reaction to Erysiphe polygoni. The results showed heterogeneity among families to all traits studied. This heterogeneity allows the selection of families adapted to the winter conditions. The genetic correlation between number of the days to flowering and reaction to Erysiphe polygoni is low and negative. The estimates of heritabilities (broad sense) are relatively high to all traits in the two sets evaluated. The heritability (broad sense) of normal cycle families is similar to realized heritability.